PENGEMBANGAN BAAMBOOZLE BERBASIS CANVA MATERI SEL UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMPN 8 PEMATANGSIANTAR - Renova Manurung; Gunaria Siagian; Mastiur Verawaty Silalahi (Smart Education, 2025)
Abstract: Media suitability, student responses, and learning outcomes are the objectives of this scientific study. The background of the study was based on the decline in learning outcomes for the material. It was found that 33.8% of students reached the Minimum Completion (KKM), and the implementation of the teaching and learning process was still conventional. Development research is a type of development method with the ADDIE approach which includes the stages of analysis, design, development, implementation and evaluation The research subjects were students of grades VIII-2 (experimental class) and VIII-3 (control class) who had passed the sample selection process by random sampling. The research instruments included non-tests and tests (pretest and posttest). Data identification used media feasibility tests, student response questionnaires, and final scores as non-parametric statistical tests as answers to temporary decisions. The research results proved that the Canva-based Baamboozle teaching material was said to be very suitable for use based on the assessment decisions of material experts and media experts. Most students gave positive responses after implementing the media in the classroom, indicating a reciprocal response and involving learning participation. This resulted in differences in the experimental class that were not found in the control class. The final decision was based on the Mann-Whitney test results <0.000. Therefore, Ha was accepted and Ho was rejected. Keywords: Baamboozle, Canva, animal cells, plant cells Abstrak: Kelayakan media, respon siswa, dan nilai belajar adalah tujuan dari kajian ilmiah ini. Latar belakang penelitian berlandaskan pada menurunya nilai hasil belajar terhadap materi tersebut. Diketahui 33,8% siswa mencapai KKM, serta penerapan proses belajar mengajar masih konvensional. Penelitian pengembangan adalah jenis metode pengembangan dengan pendekatan ADDIE yang mencakup tahap analisis, desain, pengembangan, penerapan, dan evaluasi. Subjek penelitian adalah siswa kelas VIII-2 (kelas eksperimen) dan VIII-3 (kelas control) yang sudah melewati proses pemilihan sample secara random sampling. Instrumen penelitian meliputi non-tes dan tes (pretest dan posttest). Pengidentifikasian data memakai uji kelayakan media, angket respon siswa, serta nilai akhir sebagai uji statistik non-parametrik sebagai jawaban keputusan sementara. Hasil riset membuktikan jika bahan ajar Baamboozle berbasis Canva disebutkan sangat layak dipergunakan berdasarkan keputusan penilaian validador ahli. Kebanyakan respon positif diberikan siswa setelah penerapan media di dalam kelas yang,menandakan adanya respon timbal balik serta melibatkan partisipasi belajar. Hal ini menimbulkan adanya perbedaan kelas eksperimen yang tidak dimiliki kelas kontrol. Keputusan akhir diperoleh berlandaskan hasil uji Mann-Whitney <0,000. Oleh karena itu, Ha diterima dan Ho ditolak. Kata Kunci : Baamboozle, Canva, sel hewan, sel tumbuhan